City skew and homeowner subsidy removal - Alexander Daminger; Kristof Dascher (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
Many countries subsidize homeownership, and Germany is no exception. However, for an interlude of 12 years Germany also paused its subsidy. Over these twelve years most of the country's 100 largest cities saw their central city population expand. We explore subsidy removal's role in center revival. We assemble a large data set of population strata for a fine partition of city rings. Then we exploit the design of the subsidy (which benefited more affordable places more, and also which never benefited the young) to identify its effects on urban spatial structure. We will find that homeowner subsidy removal has strongly driven the skew of the distribution of commuting distance up. In doing so subsidy removal has also, so we will suggest, contributed to strong recent growth in both, urban rent and female labor force participation.
Keywords: R12; D72; R52; 330; Commuting Distribution; Skewness; Homeownership Subsidy; Reurbanization